PENGARUH ALOKASI DANA DESA TERHADAP JUMLAH PENDUDUK MISKIN DI KABUPATEN LEBAK - Usep Siswadi; Tian Septiantini; Firmansyah Firmansyah (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2021)
Poverty always attracts the attention of various groups, both academics and practitioners. Various theories, concepts and approaches are constantly being developed to uncover the curtain of the "mystery" of poverty. Indonesia, the problem of poverty is a social problem that is always relevant to be studied continuously. This is not only because the problem of poverty has been around for a long time and is still present in our midst now, but also because now the symptoms are increasing in line with the multidimensional crisis that is still faced by the Indonesian people.Management of village fund allocations must fulfill several management principles, each activity whose funding is taken from village fund allocations must go through open planning, implementation and evaluation on principle. Allocation of village funds must be used with the principle of frugality, direction and control, all activities and use of village fund allocations can be accounted for administratively, technically and legally. The types of activities that will be funded through village fund allocation are expected to be able to improve community service facilities, in the form of fulfilling the basis, strengthening village institutionalization and other activities needed by the village community through decision-making through deliberation.In order to increase empowerment, prosperity and equitable development in rural areas through district, provincial and central government budget funds, the district government. Provinces and centers need to realize in the APBD 10% each for village allocation funds. By allocating 10% of the funds, it is hoped that welfare and equitable development in the village can become a reality. The creation of equal distribution of development, especially in rural areas through the provincial government budget funds and the central government of 10%, will achieve a level of welfare and standard of living for people living in rural areas.The design of testing this hypothesis is assessed by the income of the null hypothesis and alternative hypotheses, the research of statistical tests and the calculation of the value of statistical tests, the calculation of hypotheses, the determination of a significant level and drawing conclusions.The hypothesis that will be used in thi